Evidence-based management of epilepsy - Schachter, Steven C. (TFM, 2011)
The clinical management of patients with epilepsy and the associated medical literature are rapidly evolving. This book includes chapters that cover the therapy of seizures when they develop after traumatic brain injury or stroke, and the treatment of concomitant depression and anxiety in patients with epilepsy